Design and control of a novel two-speed Uninterrupted Mechanical Transmission for electric vehicles. (15th June 2016) - Fang, Shengnan; Song, Jian; Song, Haijun; Tai, Yuzhuo; Li, Fei; Sinh Nguyen, Truong
Abstract: Conventional all-electric vehicles (EV) adopt single-speed transmission due to its low cost and simple construction. However, with the adoption of this type of driveline system, development of EV technology leads to the growing performance requirements of drive motor. Introducing a multi-speed or two-speed transmission to EV offers the possibility of efficiency improvement of the whole powertrain. This paper presents an innovative two-speed Uninterrupted Mechanical Transmission (UMT), which consists of an epicyclic gearing system, a centrifugal clutch and a brake band, allowing the seamless shifting between two gears. Besides, driver׳s intention is recognized by the control system which is based on fuzzy logic controller (FLC), utilizing the signals of vehicle velocity and accelerator pedal position. The novel UMT shows better dynamic and comfort performance in compare with the optimized AMT with the same gear ratios. Comparison between the control strategy with recognition of driver intention and the conventional two-parameter gear shifting strategy is presented. And the simulation and analysis of the middle layer of optimal gearshift control algorithm is detailed. The results indicate that the UMT adopting FLC and optimal control method provides a significant improvement of energy efficiency, dynamic performance and shifting comfort for EV. Highlights: We present an innovative 2-speed transmission for EVs allowing seamless gearshift. Driver׳s intention recognized based on FLC is implemented in EV. The transmission shows better dynamic and comfort performance in compare with AMT. Model predictive control and convex optimization are implemented in the controller. Results show the improvement of performance adopting FLC and optimal control.